Crisis Diplomacy from Below: Subnational Legitimacy, Legal Pluralism, and Global Multilevel Governance Dynamics - Hakim, Lukman; Negara, Purnawan Dwikora; Sirajuddin, Sirajuddin; Melati, Qatrunnada Hamparan (Jurnal Media Hukum, 2025)
This Study analyzes how subnational governments in Surabaya (Indonesia), Cebu (Philippines), and Chiang Mai (Thailand) Practice diplomacy amid crises. This study introduces the concept of crisis diplomacy from below, describing how cities navigate centralized legal systems yet engage globally during pandemics, disasters, and economic shocks. Using a Qualitative, theory-guided comparative case study based on MoUs/Lols, city-network documents, and secondary sources, this study finds that a state-centric treaty framework leaves recognition gaps but allows informal collaboration. Grounded in performance-based legitimacy, legal pluralism, multilevel governance, and actorness, cities emerge as pragmatic diplomatic actors employing soft legal tools, networks, and cultural exchanges to overcome legal and institutional constraints. Results indicate greater flexibility and responsiveness in health and disaster management, as well as clearer paths for sustainable development. This study contributes to the field by conceptualizing crisis diplomacy from a bottom-up perspective and proposing hybrid legal mechanisms to legitimize city-level cooperation during crises without compromising sovereignty, thereby advancing an inclusive model of global governance that recognizes subnational actors, particularly in Southeast Asia.